1997
DOI: 10.1142/s0218196797000150
|View full text |Cite
|
Sign up to set email alerts
|

On the Algebra of Semigroup Diagrams

Abstract: In this work we enrich the geometric method of semigroup diagrams to study semigroup presentations. We introduce a process of reduction on semigroup diagrams which leads to a natural way of multiplying semigroup diagrams associated with a given semigroup presentation. With respect to this multiplication the set of reduced semigroup diagrams is a groupoid. The main result is that the groupoid [Formula: see text] of reduced semigroup diagrams over the presentation S = <X:R> may be identified with the fund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 0 publications
1
46
0
Order By: Relevance
“…A diagram is called reduced if it does not contain dipoles. By reducing dipoles, a diagram can be transformed into a reduced diagram, and a result of Kilibarda [Kil94] proves that this reduced form is unique. If ∆ 1 , ∆ 2 are two diagrams for which ∆ 1 • ∆ 2 is well defined, let us denote by ∆ 1 · ∆ 2 the reduced form of ∆ 1 • ∆ 2 .…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…A diagram is called reduced if it does not contain dipoles. By reducing dipoles, a diagram can be transformed into a reduced diagram, and a result of Kilibarda [Kil94] proves that this reduced form is unique. If ∆ 1 , ∆ 2 are two diagrams for which ∆ 1 • ∆ 2 is well defined, let us denote by ∆ 1 · ∆ 2 the reduced form of ∆ 1 • ∆ 2 .…”
Section: Preliminariesmentioning
confidence: 99%
“…The definition of diagram groups was first given by Meakin and Sapir, with the first results found by their student Kilibarda in her thesis [Kil94]. Although it was proved that diagram groups define a large class of groups with strong properties [GS97,GS99,GS06a,GS06b], very little is known on their geometric properties.…”
Section: Introductionmentioning
confidence: 99%
“…It was implicitely defined by Squier in [31]. The same complex was independently constructed by Kilibarda [17,18] and Pride [26]. The important role of this complex is justified by the fact that equal diagrams over P correspond to homotopic paths in K(P).…”
mentioning
confidence: 99%
“…The important role of this complex is justified by the fact that equal diagrams over P correspond to homotopic paths in K(P). The following Kilibarda's theorem [17,18] plays an important role in this paper: The diagram group D(P, w) is isomorphic to the fundamental group π 1 (K, w) of the Squier complex K = K(P).…”
mentioning
confidence: 99%
“…A typical element of this monoid is a congruence class W& (WPF), and we have an isomorphism from this monoid to G, given by W& U 3 W N W P F X We will often identify W& and [W]N (if no confusion can arise) and will denote this element by " W. Now in [12] (see also [11]) we associated with any monoid presentation a 2-complex h( ) (``the 2-complex of monoid pictures'') and we showed that the ®rst homology group H 1 (h( )) has considerable signi®cance. The fundamental groups of h( ) are also of considerable interest and have been investigated by Guba and Sapir [7], and Kilibarda [8].…”
mentioning
confidence: 99%